1998
DOI: 10.1093/geronb/53b.4.p223
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the Effects of Knowledge on On-Line Reading Strategies

Abstract: The effects of knowledge on on-line reading strategies and the relation of these effects to subsequent memory performance among young and elderly adults were investigated. Participants read passages with vague, ill-defined content word-by-word on a computer screen for immediate recall and reading times were recorded. High-knowledge (HK) readers received passage titles that clarified the content and low-knowledge (LK) readers did not. Reading strategy was found to be related to age, knowledge, and subsequent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
4
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 40 publications
11
123
4
1
Order By: Relevance
“…Other studies have shown that older adult readers tend to spend relatively less time on the ends of syntactic constituents such as ends of clauses and sentences than do young readers (L. M. S. Miller & Stine-Morrow, 1998;Stine, 1990;Stine & Hindman, 1994). Although the older adults in the present study paused significantly longer at the ends of sentences than at the other boundary types, they spent less time than the young at the ends of clauses.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Other studies have shown that older adult readers tend to spend relatively less time on the ends of syntactic constituents such as ends of clauses and sentences than do young readers (L. M. S. Miller & Stine-Morrow, 1998;Stine, 1990;Stine & Hindman, 1994). Although the older adults in the present study paused significantly longer at the ends of sentences than at the other boundary types, they spent less time than the young at the ends of clauses.…”
Section: Discussioncontrasting
confidence: 67%
“…Finally, reading studies have indicated that both young and older adults' reading times decrease as more ofa passage is read (L. M. S. Miller & Stine-Morrow, 1998;Stine et al, 1995;Stine et al, 1996). This pattern of data has been interpreted in the reading literature as reflecting the initial construction ofa situational discourse model early in the texts that facilitates the subsequent encoding of text material (e.g., Gernsbacher, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sizes of the reading time effects were comparable in the younger and the older adults (see also Stine-Morrow, Loveless, &Soederberg, 1996, andStine-Morrow, 1998, for a similar outcome using serial position as a measure of situation model processing). That is, when the narratives described shifts in space or time, there was a new agent or goal introduced in the stories, or there was a break in the causal structure, people slowed down when reading these passages.…”
Section: Creation Of Dynamic Situation Models In Texts: Updatingmentioning
confidence: 74%
“…However, these constraints must be contextualized in terms of a system that may be relatively more sensitive to socioemotional goals in learning (e.g., Adams et al, 2002), more attuned to situational features (e.g., Dijkstra, Yaxley, Madden, & Zwaan, 2004;Stine-Morrow, Morrow, & Leno, 2002;Stine-Morrow et al, 2004), and more adept at exploiting knowledge (Miller & Stine-Morrow, 1998;Miller, Cohen, & Wingfield, in press;Miller, Stine-Morrow, Kirkorian, & Conroy, 2004) and the higher-order structures of discourse (Stine-Morrow, Miller, Gagne, & Hertzog, submitted). Table 2 Hierarchical Regressions Predicting Recall Performance and Encoding Efficiency …”
Section: Discussionmentioning
confidence: 99%